2008
DOI: 10.1016/j.molcel.2008.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Organization of an Activator-Bound RNA Polymerase Holoenzyme

Abstract: SummaryTranscription initiation involves the conversion from closed promoter complexes, comprising RNA polymerase (RNAP) and double-stranded promoter DNA, to open complexes, in which the enzyme is able to access the DNA template in a single-stranded form. The complex between bacterial RNAP and its major variant sigma factor σ54 remains as a closed complex until ATP hydrolysis-dependent remodeling by activator proteins occurs. This remodeling facilitates DNA melting and allows the transition to the open complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
113
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(123 citation statements)
references
References 58 publications
10
113
0
Order By: Relevance
“…The determination of the transcriptional start sites allowed us to identify two 54 -dependent Ϫ24/Ϫ12 elements upstream of orp1 and orp2, respectively. Both sequences are similar to the published conservative regions of the bacterial 54 -dependent promoter (5,7,35). In addition, we experimentally demonstrated that the expression of orp1 and orp2 was dependent on the 54 -RNA polymerase.…”
Section: Vol 193 2011 54 Regulation Of the Desulfovibrio Orp Gene Csupporting
confidence: 71%
“…The determination of the transcriptional start sites allowed us to identify two 54 -dependent Ϫ24/Ϫ12 elements upstream of orp1 and orp2, respectively. Both sequences are similar to the published conservative regions of the bacterial 54 -dependent promoter (5,7,35). In addition, we experimentally demonstrated that the expression of orp1 and orp2 was dependent on the 54 -RNA polymerase.…”
Section: Vol 193 2011 54 Regulation Of the Desulfovibrio Orp Gene Csupporting
confidence: 71%
“…The work described here represents the successful application of the method to an intact, complete activator-dependent transcription initiation complex bound to promoter DNA. Single-particle EM has also recently been applied to structure determination of E. coli 54 RNAP in complex with an AAAϩ activator (43) and Bacillus subtilis RNAP core in complex with elongation factor NusA (44). The methods defined in this study should be applicable to analysis of additional bacterial transcription complexes, to define binding sites for regulators of bacterial transcription, and to define the structural consequences of binding of regulators of bacterial transcription.…”
Section: Discussionmentioning
confidence: 99%
“…3. The contour of the shape representing a monomer is merely descriptive and was derived from the outer outlines of the cryo-electron microscopy r 54 densities D1, D2 and D3, and the connecting density between the RNAP claws (named Db) shown in Figure 1D of Bose et al [11], which overall reconstruct the shape of r 54 in the E. coli r -based hybrids expressed from pEG202 and pJG4-5 was performed by western blotting (see below) using antibodies against LexA and HA, respectively. For western blotting, protein were separated by SDS/PAGE [10% acrylamide/bisacrylamide 29 : 1, 0.1% SDS, in 19 Tris/glycine buffer (Bio-Rad, Hercules, CA, USA)]and transferred via a semi-dry apparatus (Fastblot B33; Biometra, Goettingen, Germany) onto nitrocellulose membranes (Protran; Whatman, GE Healthcare, Uppsala, Sweden) with fixed 1.66 mAÁcm À2 for 1 h. The membranes were blocked with NaCl/P i with 0.05% Tween-20 and 5% skimmed milk, and incubated with antibodies in NaCl/P i with 0.05% Tween-20 and 0.5% skimmed milk.…”
Section: Proteins and Protein Analysesmentioning
confidence: 99%
“…-RNAP, r 54 region I localizes in the channel between the b and b' subunits and prevents entry of single-stranded template DNA into the active site of RNAP [10,11]. This accounts for the inability of the closed complex of r 54 -RNAP to transcribe.…”
mentioning
confidence: 99%
See 1 more Smart Citation